2019
DOI: 10.1182/bloodadvances.2019000540
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid synergizes with the unfolded protein response and oxidative stress to induce cell death in FLT3-ITD+ AML

Abstract: Key Points RA synergizes with the N-glycosylation inhibitor tunicamycin and ATO to induce AML cell death via generation of ER and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…A very recent article has demonstrated that a combined treatment consisting of low concentrations of retinoic acid (RA), of the ER stressor tunicamycin, and of arsenic trioxide (ATO), led to ER and oxidative stresses as well as to UPR in AML cells expressing fusion proteins such as MLL-AF4, MLL-AF6, MLL-AF9, or FLT3-internal tandem duplication (ITD), alone or in combination. The treatment caused an accumulation of mutant FLT3 protein in the ER and decreased the colony-forming capacity of primary leukemic cells bearing the FLT3-ITD mutation without affecting healthy human HPCs isolated from the BM [127]. It is worth highlighting here that the FLT3-ITD fusion protein is detected in~25-30% of AML cases and is a misfolded protein mostly retained in the ER.…”
Section: Therapeutic Strategies For Amlmentioning
confidence: 83%
“…A very recent article has demonstrated that a combined treatment consisting of low concentrations of retinoic acid (RA), of the ER stressor tunicamycin, and of arsenic trioxide (ATO), led to ER and oxidative stresses as well as to UPR in AML cells expressing fusion proteins such as MLL-AF4, MLL-AF6, MLL-AF9, or FLT3-internal tandem duplication (ITD), alone or in combination. The treatment caused an accumulation of mutant FLT3 protein in the ER and decreased the colony-forming capacity of primary leukemic cells bearing the FLT3-ITD mutation without affecting healthy human HPCs isolated from the BM [127]. It is worth highlighting here that the FLT3-ITD fusion protein is detected in~25-30% of AML cases and is a misfolded protein mostly retained in the ER.…”
Section: Therapeutic Strategies For Amlmentioning
confidence: 83%
“…Experiments with cell lines, xenografts, and primary AML samples indicated that inhibition of the SUMO pathway may sensitize AML cells to atRA [97]. Similarly, the endoplasmatic reticulum-stress inducing drug tunicamycin was reported to cooperate with atRA and ATO to inhibit the clonogenic capacity and to promote death of human AML cell lines and primary AML cells, particularly those with a FLT3-ITD [98]. Another set of in vitro experiments led to the suggestion that inhibition of the histone acetyltransferase GCN5 and/or the lysine demethylase LSD1 augmented the antileukemic activities of atRA [99].…”
Section: Atra In Non-apl Aml: Preclinical Studiesmentioning
confidence: 99%
“…A number of studies have implicated that ER stress is of vital importance in the treatment of AML. For example, the combination of ER stress activator tunicamycin with conventional anti-AML drugs, such as arsenic trioxide and retinoic acid, has been found to induce cell apoptosis significantly [18,19]. A previous study has observed that GSK-J4 can promote the differentiation of neuroblastoma cells via ER stress [20], indicating that ER stress plays a potential role in GSK-J4 treatment.…”
mentioning
confidence: 99%